Organization Digital Culture as Convergent Paradigm for Law and Economy - E. M. Borodinskaya; A. N. Fironov (Цифровая трансформация)
The concept of digital culture refers to a transdisciplinary field of research located at the intersection of the complex of social sciences and the humanities (culturology, philosophy, history, jurisprudence, economics, etc.). This article examines the essence and content of the digital culture of an organization as a holistic phenomenon through the prism of a transdisciplinary connection between the economic and legal aspeof the problem. The essence and interrelation of the terms “information culture”, “digital culture”, “legal culture” are analyzed. A methodology for assessing the level of digital culture of an organization’s ecosystem is proposed.